2012
DOI: 10.1177/1468797612454250
|View full text |Cite
|
Sign up to set email alerts
|

Nightlife tourism: A mixed methods study of young tourists at an international nightlife resort

Abstract: Drawing on data generated through quantitative and qualitative methods, this article explores the prevalence and experiences of substance use, casual sex, commercial sex, and health problems among young Danish tourists at an international nightlife resort in Bulgaria. The article argues that the risks the tourists take should not be interpreted as a symptom of nihilism, pathology, or escapist inclinations. Rather, the tourists intentionally engage in certain forms of risk in order to move far beyond the mundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…In recent years, studies identifying the type and extent of harms experienced by young nightlife users across Europe have started to emerge (Hughes et al, 2008;2011a;Schnitzer et al, 2010;Tutenges, 2012). While studies in Scotland (Forsyth, 2006;Forsyth, Cloonan, & Barr, 2005) have assessed the relationships between observed aggression and recorded crime within nightlife venues and individual, social and environmental factors, to our knowledge this is the first observational study to examine a range of harms within venues and their links with staffing, customer and environmental characteristics across multiple European cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies identifying the type and extent of harms experienced by young nightlife users across Europe have started to emerge (Hughes et al, 2008;2011a;Schnitzer et al, 2010;Tutenges, 2012). While studies in Scotland (Forsyth, 2006;Forsyth, Cloonan, & Barr, 2005) have assessed the relationships between observed aggression and recorded crime within nightlife venues and individual, social and environmental factors, to our knowledge this is the first observational study to examine a range of harms within venues and their links with staffing, customer and environmental characteristics across multiple European cities.…”
Section: Discussionmentioning
confidence: 99%
“…However, more minor incidents that are often accepted or unreported, such as patrons arguing or being too drunk to walk (Hesse, Tutenges, Pedersen, & Kofoed, 2012;Hughes et al, 2008;Tutenges, 2012), have the potential to escalate into more serious problems, including violence and unintentional injury. Research shows that a large proportion of alcohol-related problems in nightlife are often focused around a small number of venues (Briscoe & Donnelly, 2003;Newton & Hirschfield, 2009), suggesting that certain factors about these venues may impact on patrons' experience of harms.…”
mentioning
confidence: 99%
“…Park, Choi, and Lee (2008) argue the economic effects of installing architectural outdoor lighting such as increasing tourist attraction. Urban nightlife is an important factor in attracting tourists (Tutenges, 2012). In fact, with the advent of urban nightlife, urban lighting improves the urban nightlife, which will attract tourists and, as a result, promote and cause economic improvement districts.…”
Section: Eids As a City Branding Factormentioning
confidence: 99%
“…Thus, adventurous and physically demanding travel experiences are frequently central to the travel narratives of young male travellers (for example, see Noy, 2007). Likewise, research on young Danish tourists in coastal resorts in Bulgaria found that men reported higher levels of alcohol, tobacco and illicit drug use on holiday (Tutenges, 2012) and men were also found to be more likely to visit strip clubs and sex shows (Hesse and Tutenges, 2011).…”
Section: Risk and Adventurementioning
confidence: 99%
“…In spite of this, ongoing news coverage continues to raise concerns about the strains placed on British consular services by stag tour groups in Eastern European cities (Sherman, 2006;Channel 4 News, 20 September 2007). Interestingly, Tutenges (2012) observes that the negative reputation of such destinations cultivated in the media in fact fosters interest among young male tourists drawn by the allure of a holiday environment where drunkenness, disinhibition and spontaneity are encouraged and accepted. Indeed, such negative portrayals of Eastern European cities ultimately prove counterproductive when so readily fed into narratives of masculine travel which valorise risk, danger and adventure.…”
Section: Risk and Adventurementioning
confidence: 99%